2024
DOI: 10.1038/s41598-024-53894-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of circulating tumor HPV16DNA levels and quantitative PET parameters in patients with HPV-positive head and neck squamous cell carcinoma

Mitsuaki Tatsumi,
Hidenori Tanaka,
Yukinori Takenaka
et al.

Abstract: Circulating tumor DNA (ctDNA), which circulates in the blood after being shed from cancer cells in the body, has recently gained attention as an excellent tumor marker. The purpose of this study was to evaluate whether ct human papillomavirus (HPV) 16 DNA (ctHPV16DNA) levels were associated with quantitative PET parameters in patients with HPV-positive head and neck (HN) squamous cell carcinoma (SCC). Fifty patients with oropharyngeal SCC (OPSCC) and 5 with SCC of unknown primary (SCCUP) before treatment were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…However, Tatsumi et al demonstrated that ctHPV16 levels correlated with the whole-body tumor burden visualized by 18F-FDG PET-CT. They suggested that ctHPV16 DNA and PET-CT may complement each other, which would be useful in post-treatment management decisions [ 33 ]. Several studies have highlighted a positive correlation between high metabolic tumor burden and ctDNA detection in patients with locally advanced, previously untreated HNSCC [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Tatsumi et al demonstrated that ctHPV16 levels correlated with the whole-body tumor burden visualized by 18F-FDG PET-CT. They suggested that ctHPV16 DNA and PET-CT may complement each other, which would be useful in post-treatment management decisions [ 33 ]. Several studies have highlighted a positive correlation between high metabolic tumor burden and ctDNA detection in patients with locally advanced, previously untreated HNSCC [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that ctHPV16 DNA and PET-CT may complement each other, which would be useful in post-treatment management decisions [ 33 ]. Several studies have highlighted a positive correlation between high metabolic tumor burden and ctDNA detection in patients with locally advanced, previously untreated HNSCC [ 33 , 34 , 35 ]. In the era of precision oncology, multiparametric tests will be helpful in creating prognostic and predictive algorithms in the management of patients with ctHPV-positive HNSCC [ 34 ].…”
Section: Discussionmentioning
confidence: 99%